Time Trends in Prevalence of Anemia in Preschool Children in India - Kalaivani, K.; Ramachandran, Prema (Annals of the National Academy of Medical Sciences (India), 2019)
Introduction Anemia is a major public health problem in Indian children. India introduced iron-folic acid supplementation for preschool children in the 1970s. In 1990, the component of detection and treatment of anemia was added. It is important to assess the impact of these programs on the prevalence of anemia in preschool children.Materials and Methods Prevalence of anemia in preschool children at the national and state level was tabulated from National Family Health Survey (NFHS) 2, 3, and 4 national and state reports. Raw data from NFHS 2, 3, 4; District Level Household Survey (DLHS) 2 and 4; and Annual Health Survey and its Clinical Anthropometric and Biochemical component (AHS CAB) were analyzed to find out the changes in mean Hb, prevalence of anemia, and frequency distribution of Hb.Results Compared with NFHS 2, there was a 5% increase in prevalence of anemia, 0.3 g/dL fall in mean Hb levels, and a small shift to the left in frequency distribution of Hb levels in NFHS 3. There was a 10% reduction in prevalence of anemia in NFHS 4 as compared with NFHS 3. Comparison between DLHS 2, DLHS 4, and AHS CAB showed that there was a 15 to 20% reduction in prevalence of anemia, approximately 1 g/dL increase in mean Hb and a shift to the right in distribution of Hb levels.Conclusion There has been some improvement in Hb levels in preschool children in the last decade, but prevalence of anemia continues to be very high. Effective implementation of the comprehensive package of interventions recommended in National Iron Plus Initiative (NIPI) guidelines is urgently needed to achieve rapid and sustained reduction in anemia.
Keywords: dietary intake of iron; dietary intake; iron fortified iodized salt; test and treat strategy